2006
DOI: 10.1108/02640470610707277
|View full text |Cite
|
Sign up to set email alerts
|

Preparedness for personalizing content in IIT libraries

Abstract: Purpose -The paper aims to assess the level of preparedness of the Central Libraries of the Indian Institutes of Technology (IITs) to personalize content and seeks to determine whether the personalization service prototype being developed at IIT Kharagpur can be extrapolated to the remaining IITs. Design/methodology/approach -A questionnaire was sent to the Librarians of the seven IITs, designed to compare the available information resources and services, with special emphasis on user interests and personaliza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…The criteria for selecting Delphi panel members included individuals who specialize in digital libraries and services personalization. The members of the Delphi panel were Iranian experts who had one or more of the following characteristics: Kamali (2015) Creating personalized content through: access to databases, e-journals, reference works, other information sources and possibility to add intended resources to the list of documents and personal library Jeevan and Padhi (2006); Jeevan (2008); Morgan (1999); Di Giacomo et al (2001); Ghaphery and Ream (2000); Rozic-Hristovski et al (2003); Lan and Ping (2009); Holmström (2002) Defining access levels based on the role assigned to the user/the services need to be tailored according to each and every user's rights and privileges Tonta (2004); Janmohammadi (2018) Providing the possibility to view the user's loan, reservation and return documents Koochaki (2014); Abam and Arastoopoor (2015); Janmohammadi (2018) Providing reports of user's renewed, reserved and returned documents Janmohammadi (2018); Abam and Arastoopoor (2015); Koochaki (2014) Possibility to renew and reserve the library documents by the user Janmohammadi (2018) Viewing the user's delay, fines and reckoning Koochaki (2014); Abam and Arastoopoor (2015) User's following about purchase suggestions from the library Abam and Arastoopoor (2015); Koochaki (2014); Shahraki Sanavi (2016) Following up the correction suggestion Abam and Arastoopoor (2015); Koochaki (2014) Providing feedback and suggestions to the library through interactive forms and other available tools Janmohammadi (2018) Multilingual support Rozic-Hristovski et al (2003); Shahraki Sanavi (2016) Sending a variety of messages from the library to the user including public message, librarian message, specialized librarian message (related to user's major), messages related to library events Morgan (1999); Di Giacomo et al (2001); Rozic-Hristovski et al (2003);…”
Section: Methodsmentioning
confidence: 99%
“…The criteria for selecting Delphi panel members included individuals who specialize in digital libraries and services personalization. The members of the Delphi panel were Iranian experts who had one or more of the following characteristics: Kamali (2015) Creating personalized content through: access to databases, e-journals, reference works, other information sources and possibility to add intended resources to the list of documents and personal library Jeevan and Padhi (2006); Jeevan (2008); Morgan (1999); Di Giacomo et al (2001); Ghaphery and Ream (2000); Rozic-Hristovski et al (2003); Lan and Ping (2009); Holmström (2002) Defining access levels based on the role assigned to the user/the services need to be tailored according to each and every user's rights and privileges Tonta (2004); Janmohammadi (2018) Providing the possibility to view the user's loan, reservation and return documents Koochaki (2014); Abam and Arastoopoor (2015); Janmohammadi (2018) Providing reports of user's renewed, reserved and returned documents Janmohammadi (2018); Abam and Arastoopoor (2015); Koochaki (2014) Possibility to renew and reserve the library documents by the user Janmohammadi (2018) Viewing the user's delay, fines and reckoning Koochaki (2014); Abam and Arastoopoor (2015) User's following about purchase suggestions from the library Abam and Arastoopoor (2015); Koochaki (2014); Shahraki Sanavi (2016) Following up the correction suggestion Abam and Arastoopoor (2015); Koochaki (2014) Providing feedback and suggestions to the library through interactive forms and other available tools Janmohammadi (2018) Multilingual support Rozic-Hristovski et al (2003); Shahraki Sanavi (2016) Sending a variety of messages from the library to the user including public message, librarian message, specialized librarian message (related to user's major), messages related to library events Morgan (1999); Di Giacomo et al (2001); Rozic-Hristovski et al (2003);…”
Section: Methodsmentioning
confidence: 99%
“…Kanamadi and Kumbar (2006) reasoned their findings with "cursory approach of librarians' in developing academic online services at Mumbai business school libraries". Moreover, Jeevan and Padhi (2006) assessed the preparedness of premier IIT libraries in India on "personalised content delivery and information services and found this customised service prototype to be in nascent stage among the Indian Institutes of Technology libraries". In studying the library automation and networking in India, Vyas (1997) found that "academic libraries are not under pressure as against the scientific and technical libraries".…”
Section: Reportedmentioning
confidence: 99%
“…The systems aim to search automatically and retrieve information resources of interest from online journals and databases for the faculty members of IIT, Kharagpur who are actively engaged in the frontier areas of science and technology teaching and research using web usage mining, proxy data, and vector space modelling. Jeevan and Padhi (2006a) review the literature on content personalisation and Jeevan and Padhi (2006b) report on the preparedness of other libraries in IITs for this development.…”
Section: Introductionmentioning
confidence: 99%